KEY DETERMINANTS OF ESIM ADOPTION INTENTION AMONG INDONESIAN CONSUMERS - Weku, Jupiter; Mandagi, Deske W. (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study examines the factors influencing eSIM adoption intention among consumers in Indonesia, where the technology remains relatively new. Using a quantitative research design, data was gathered from 150 respondents via a structured questionnaire. The analysis, conducted using Structural Equation Modeling (SEM), identifies key determinants, including perceived ease of use, perceived benefits, and environmental awareness. Results show that ease of use is the most significant factor driving eSIM adoption, with consumers favoring the simplicity and efficiency of the technology. Environmental awareness also plays a critical role, as consumers appreciate the eco-friendly aspect of eSIMs, which eliminates the need for plastic SIM cards. Price sensitivity is another major determinant, with cost considerations influencing adoption decisions. The study provides valuable insights for mobile network operators and marketers, suggesting that promoting the environmental and practical benefits of eSIMs could accelerate adoption. These findings contribute to the broader understanding of technology adoption in emerging markets and offer guidance on optimizing marketing strategies to foster consumer acceptance of eSIM technology.